2007
DOI: 10.1080/14756360600920180
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania amazonensis trypanothione reductase: Evaluation of the effect of glutathione analogs on parasite growth, infectivity and enzyme activity

Abstract: Department of Chemistry, UFRJ, Rio de Janeiro, Brazil Abstract Trypanothione reductase (TR) is a major enzyme in trypanosomatids. Its substrate, trypanothione is a molecule containing a tripeptide (L-glutamic acid-cysteine-glycine) coupled to a polyamine, spermidine. This redox system (TR/Trypanothione) is vital for parasite survival within the host cell and has been described as a good target for chemotherapy anti-Leishmania. The use of tripeptides analogs of glutathione would result in a decrease in trypanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In L. amazonensis, reduced glutathione (GSH) is a component of trypanothione, a major antioxidant of this parasite, 21 and intracellular GSH levels can be increased by treatment with the antioxidant N-acetyl-L-cysteine (NAC). 22 To confirm that the inhibitory effects of 1 are mediated by ROS production, L. amazonensis promastigotes were preincubated with GSH or NAC (300 μM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In L. amazonensis, reduced glutathione (GSH) is a component of trypanothione, a major antioxidant of this parasite, 21 and intracellular GSH levels can be increased by treatment with the antioxidant N-acetyl-L-cysteine (NAC). 22 To confirm that the inhibitory effects of 1 are mediated by ROS production, L. amazonensis promastigotes were preincubated with GSH or NAC (300 μM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been suggested that to sustain active infections within macrophages, parasites should preserve a detectable expression of trypanothione reductase (TR) (Castro-Pinto et al, 2007) and a high level of nitric oxide (NO) production (Genestra et al, 2006). TR and NO help parasites to maintain infection by neutralizing toxic free radicals (nitrogenated and oxygenated) produced by host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from our group have already shown that noninfective parasites have a low expression of TR, as well as low production of NO. These data could explain why parasites with no detectable metacyclic forms were unable to sustain the in vitro and in vivo infections (Genestra et al, 2006;Castro-Pinto et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In Trypanosomes and Leishmanias, trypanothione plays a central role in parasite protection against mammalian host defence systems by recycling trypanothione disulfide by the enzyme trypanothione reductase (TR). 60 Although Kinetoplastida parasites lack GSH reductase, they maintain significant levels of GSH. We also verified the higher resistance of axenic amastigotes to SNP (Figure 3) than promastigotes, corroborating with recent results of our Laboratory, that showed higher TR activity in axenic amastigotes than in promastigotes.…”
Section: Discussionmentioning
confidence: 99%